Analisa Pengaruh Pemanfaatan Hotspot Terhadap Indek Prestasi Mahasiswa Universitas Tiga Serangkai - Kustanto; Salim; Dwi Remawati (Redtech Putra Benua, 2026)
For the academic community at universities, particularly at Tiga Serangkai University, internet-based learning has become a mandatory part of a lecturer's e-learning program. To support this learning system, hotspot facilities are needed that can be accessed by both students and lecturers. The research questions in this activity are: (a) How many students have utilized hotspot facilities for study purposes (such as searching for literature for theses or assignments), (b) How much influence hotspot facilities have on the achievement index of students at Tiga Serangkai University. The purpose of this study was to determine the effect of hotspot facilities provided by the academic community on student achievement index. The results of the SPSS analysis indicate that hotspot facilities on campus have a 3,6% influence on student achievement index, while 86,4% is influenced by other factors not examined. Meanwhile, the SWOT analysis results indicate that the development of hotspot facilities draws considerable strength from the institution's existing facilities and is supported by the e-learning model implemented by lecturers. This allows the e-learning process at Tiga Serangkai University to run smoothly and effectively implement the institution's quality policy, thanks to consistently up-to-date information via the internet, which can be easily and flexibly accessed, particularly on campus (via Wi-Fi).